'Pay for It Heavily': Does U.S. Support for Israel Lead to Anti-American Terrorism?. Issue 2 (17th February 2020) - Meierrieks, Daniel; Gries, Thomas
ABSTRACT: After the 9/11 attacks in particular, there has been a controversial discussion in the academic and public arena on whether the United States' close relationship with Israel has made it a likelier target of transnational terrorism. Indeed, foreign terrorist organizations with various ideological profiles have repeatedly justified attacks against U.S. interests as punishment for the (purported) special relationship between the United States and Israel. We analyze the effect of various measures of U.S. support for Israel (e.g. U.S. military assistance to Israel) on anti-American terrorism for the period 1970–2014. Using both time-series and panel approaches, we do not find that more U.S. support for Israel systematically translates into more anti-American terrorism. Rather, other systemic (e.g. U.S. dominance in the international system) and local conditions (e.g. local state failure) are found to predict the patterns of anti-American terrorism. However, as a qualification to these general findings, we also provide some (preliminary) evidence that for terrorism originating from the Middle East and Northern Africa a favorable U.S. policy stance towards Israel may indeed contribute to more anti-American terrorism.